Quantitative Structure-Activity Relationship Analysis of Organophosphate Insecticides Using Electronic and Molecular Parameters - Wibowo, Yari Mukti; Mudasir,; Pranowo, Harno Dwi (UI Scholars Hub, 2017)
Quantitative Structure-Activity Relationship (QSAR) analysis of organophosphate derivatives, and their insecticide activities, was performed using electronic and molecular parameters. The series of organophosphate derivatives and their activities were obtained from literature. The semi-empirical AM1 method was used to model the structure of organophosphate derivatives and calculate the parameters of QSAR. Multiple linear regression (MLR) analysis was performed on the electronic and molecular parameters as well as the activities of the organophosphate insecticides to derive the QSAR model. The best QSAR equation model was used to design, in silico, new insecticide molecules of organophosphate derivatives with higher insecticidal activity. A new insecticide molecule, 4-(diethoxy phosphoryloxy) benzene sulfonic acid, -Log LD50 = 7.344, had the highest insecticidal activity. Lastly, we recommend synthesizing and testing the new insecticide molecule further in the laboratory.